2017
DOI: 10.1016/j.buildenv.2017.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behavior of green roofs under Nordic winter conditions

Abstract: To understand how green roofs affect building energy performance under cold climatic conditions, a proper thermal analysis of the roof and its components is required. To address this, we measured the thermal conductivity of each layer of experimental green roofs, as well as the equivalent thermal resistance of the complete green roof system during winter conditions in southern Finland. Green roofs were compared to bare roofs (without substrate, vegetation and other green roof layers) to assess the basic functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…It is found to reduce the heat loss by about 19% compared to traditional roofs. In Collins et al [72], the thermal properties of green roofs in sub-zero temperatures and snow cover are tested. It is found that freezing the substrate actually decreases heat flux, due to a lower thermal bridging between frozen particles than in suspended water (bridge water effect).…”
Section: Insulationmentioning
confidence: 99%
“…It is found to reduce the heat loss by about 19% compared to traditional roofs. In Collins et al [72], the thermal properties of green roofs in sub-zero temperatures and snow cover are tested. It is found that freezing the substrate actually decreases heat flux, due to a lower thermal bridging between frozen particles than in suspended water (bridge water effect).…”
Section: Insulationmentioning
confidence: 99%
“…This research aimed to evaluate the combined effect of green roofs and green walls, and two sets of experiments were performed in Rio de Janeiro, Brazil at the Oswaldo Cruz Foundation (Fiocruz) and at the Previous studies evaluated the thermal aspects of vegetated prototypes [22][23][24]42,43]. Due to lack of space and so that the experimental setup would have the same exposure of solar radiation without any neighbourhood shading, the evaluation of the thermal benefits of green roof and walls was performed on an existing building roof.…”
Section: Research Methodology and Experimental Designmentioning
confidence: 99%
“…Coutts et al [24] compared the insulating properties, radiation, and surface energy balance of four experimental rooftops, including a green roof planted with sedum. Collins et al [25] measured the thermal conductivity and equivalent thermal resistance of the green roof system during winter conditions to understand how green roofs affect building energy performance under cold climatic conditions. Dvorak et al [26] monitored the temperatures and soil water content of three types of plants and one unplanted control module to understand rooftop temperature reductions of unirrigated green roofs.…”
Section: Introductionmentioning
confidence: 99%